Beliefs about lying and spreading of dishonesty: undetected lies and their constructive and destructive social dynamics in dice experiments. - Heiko Rauhut (Public Library of Science (PLoS), 2013)
Field experiments have shown that observing other people littering, stealing or lying can trigger own misconduct, leading to a decay of social order. However, a large extent of norm violations goes undetected. Hence, the direction of the dynamics crucially depends on actors' beliefs regarding undetected transgressions. Because undetected transgressions are hardly measureable in the field, a laboratory experiment was developed, where the complete prevalence of norm violations, subjective beliefs about them, and their behavioral dynamics is measurable. In the experiment, subjects could lie about their monetary payoffs, estimate the extent of liars in their group and make subsequent lies contingent on information about other people's lies. Results show that informed people who underestimate others' lying increase own lying more than twice and those who overestimate, decrease it by more than half compared to people without information about others' lies. This substantial interaction puts previous results into perspective, showing that information about others' transgressions can trigger dynamics in both directions: the spreading of normative decay and restoring of norm adherence.